The Relationship between Interest and Learning Motivation to Natural Science Learning Outcomes: A Narrative Review Study - Fitri, Fitri; Hasbi, Muhammad (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Learning outcomes are a crucial factor in determining success or failure in learning. Many students demonstrate substandard learning outcomes, falling below the minimum criteria. Learning outcomes, both favorable and unfavorable, are influenced by various elements, including motivation and interest in the learning process. Everyone has different motivations and interests in the learning process. Motivation and interest in learning are correlated with learning outcomes. Therefore, this study aims to investigate the correlation between interest, motivation, and learning outcomes, specifically in natural science subjects. The type of research conducted is qualitative with the narrative review method. The database for this narrative review consists of articles from Google Scholar, including those indexed in SINTA and other reputable international sources, published within the last ten years. The results of the study indicate that a literature evaluation of 25 publications revealed a substantial positive correlation between motivation, learning interest, and learning outcomes. Natural sciences learning outcomes are directly correlated with motivation and engagement in the learning process. Therefore, it is concluded that there is a correlation between motivation, learning interest, and natural sciences learning outcomes.